ON NEW APPROACH TO THE ESTIMATION OF CONTRIBUTION OF DIFFERENT STAGES OF TECHNOLOGICAL CYCLE TO THE SYSTEM OF THE HARDWARE PRODUCTION QUALITY CONTROL - A. N. Chichko; L. A. Feklistova; V. E. Sobolev (Литьë и металлургия)
The method for estimation of contributions of different stages of technological cycle in forming of hardware products quality based on indices Pp and Ppk for different production zones is offered.